Treatment of Other Nontuberculous Mycobacteria - Basille, Damien; Jounieaux, Vincent; Andréjak, Claire (Seminars in respiratory and critical care medicine, 2018)
Nontuberculous mycobacteria (NTM) are numerous, and for the vast majority of them, randomized studies are lacking and data regarding optimal treatment are limited. When complex (MAC) and are excluded, the main NTM are , and . Treatment is long (at least 12 months after culture conversion according to recommendations by scientific societies) and difficult (at least three drugs are required, each of which have potential adverse events). Moreover, optimal treatment is unknown for the vast majority of NTM and efficacy of treatment is not 100%. That is why, balance between benefit and risk is fundamental. For , the second most common NTM isolated in Europe, treatment is classically based on macrolides or fluoroquinolones, associated with ethambutol and rifampicin. For , the cornerstone of treatment is rifampicin, which should be associated with two other drugs: ethambutol plus isoniazid or clarithromycin. , which is common in Northern Europe, can be treated by rifampicin, ethambutol, and clarithromycin and/or fluoroquinolones.